Referral and Lost to System Rates of Two Newborn Hearing Screening Programs in Saudi Arabia - Alanazi, Ahmad A. (Int J Neonatal Screen, 2020)
Congenital hearing loss has been commonly reported as a significant health problem. Lost to system (LTS) is a major challenge facing newborn hearing screening (NHS) programs. This retrospective cross-sectional descriptive study aimed to determine the referral and LTS rates after the two-stage NHS based on transient evoked otoacoustic emissions (TEOAEs) in two main hospitals in Riyadh, Saudi Arabia (SA). NHS was performed on newborns before hospital discharge. Newborns were only rescreened if NHS initially revealed a fail/refer outcome in one or both ears. Those who failed the first and second screenings or had risk factors were referred for auditory brainstem response (ABR) testing to confirm or exclude hearing loss. In total, 20,171 newborns (40,342 ears; 52% males; 48% females) were screened, of whom 19,498 (96.66%) passed the initial screening, while 673 (3.34%) failed. Of the 673 newborns, 235 (34.92%) were LTS, and 438 (65.08%) were rescreened, of whom 269 (61.42%) failed and were referred for a comprehensive audiological assessment to confirm the existence of hearing loss. The referral rate after the initial two-stage screening was equal to 1.33%. The lack of awareness of the importance of NHS among parents seems to be the major cause behind the LTS rate. The stakeholders have to work efficiently to reduce the LTS rate.